The influence of fertilization on the soil characteristics of a calcareous chernozem in a long term experiment - Kátai, János (Acta Agraria Debreceniensis, 2010)
In the long term fertilization experiment of the University of Debrecen, Centre for Agricultural and Applied Economic Science(CAAEC) (Debrecen Látókép), the effects of a 25-year-long fertilization were examined in terms of some chemical and microbiological properties of soil. With the growing doses of fertilizers, the available nutrient content of soil increased. At the same time the pH significantly decreased, while the hidden acidity increased. Moreover, the ratio between the soil bacteria and microscopic fungi, and the occurrence of microbes also changed. The number of sensitive physiological bacteria groups decreased dramatically. These changes indicate the reactions of living organisms; they correspond to the „resistance stage” of stress effects, but in the case of nitrifying bacteria, they reach the „exhaustion stage”.